1996
DOI: 10.2500/105065896781795067
|View full text |Cite
|
Sign up to set email alerts
|

Healing Process of Sinus Mucosa after Endoscopic Sinus Surgery

Abstract: In the treatment of chronic sinusitis, the mucosa should be preserved, or, when severely damaged, only the mucosal surface removed with cutting forceps. It is especially important not to expose the surface of the bone by complete removal of the mucosa. When the mucosa is conserved, or excision is limited to only the mucosal surface, ciliated cells regenerate within 6 months. However, where the mucosa was completely removed during surgery and the bone was exposed, the area was covered with nonciliated cells, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 4 publications
1
31
0
Order By: Relevance
“…To provide for drainage of sinuses, mucosal preservation is essential, or when severely damaged, limited removal of pathological changes should be attempted. [12][13][14] Rapid postoperative recovery of mucociliary function depends on mucosal and ciliary regeneration. 14 Aggressive removal of mucosa leads to scar formation and resultant synechiae may occur between opposing damaged surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…To provide for drainage of sinuses, mucosal preservation is essential, or when severely damaged, limited removal of pathological changes should be attempted. [12][13][14] Rapid postoperative recovery of mucociliary function depends on mucosal and ciliary regeneration. 14 Aggressive removal of mucosa leads to scar formation and resultant synechiae may occur between opposing damaged surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…To provide for the drainage of the sinuses, mucosal preservation is essential, or when severely damaged, limited removal of the pathological changes should be attempted. Ciliated cells usually take 6 months to regenerate [8].…”
Section: Discussionmentioning
confidence: 99%
“…In one animal study of a Draf IIb with a drill, there was increased osteoneogenesis and frontal ostium constriction after drilling in the frontal recess, although mucociliary clearance was not affected 6 . However, Moriyama et al 8 have demonstrated that sinus mucosa regenerated over bare bone does not have normal cilia. Therefore, it is feared that the resultant denuded bone that is left after the use of a drill in the frontal recess may not have the optimum function that could be achieved if the native mucosa was preserved.…”
Section: Discussionmentioning
confidence: 99%
“…In 1967, Messerklinger 7 described the pattern of frontal sinus mucociliary clearance, which is down the lateral frontal recess wall. Consequently, the extensive frontal recess mucus membrane destruction that can be caused by drilling may damage frontal sinus mucous clearance and may create potential ostial stenosis (Moriyama et al, 8 in 1996, showed that normal functioning mucus membrane does not regenerate over bare bone). Therefore, a different method of performing a Draf III procedure (modified endoscopic intranasal Lothrop) is proposed that can be attempted before drilling in the tight confines of the frontal recess.…”
Section: Introductionmentioning
confidence: 99%